Deconstructive Theory and Its Significance in Cultivating Reading Skills - Purohi, Mouhamed Tushar (Journal of Research in Vocational Education, 2024)
Comprehending the text in a foreign language has always remained a challenge for students due to the difficult nature of the language and the ambiguity of the multiplicity of meanings. This study aims to analyse Jacques Derrida’s Deconstruction theory. The study analyses Deconstruction theory using its three principles: binary opposition, Difference, and logocentrism, to enhance EFL students’ learning skills. The researcher used a qualitative theoretical framework to conduct the study. The study analysed the works of different researchers and, based on that, formed an opinion on including the Deconstruction theory in teaching reading skills to EFL learners. The study aims to answer the two research objectives. First, analyse the deconstruction theory and its contribution to developing reading skills. Secondly, to address the elements of language, meaning and interpretation in the context of deconstruction theory. The findings showed that Deconstruction can be a valuable strategy for enhancing critical reading skills. The findings also highlighted the multiplicity of meaning in language when analysing the text through the Deconstruction approach.